Geriatric Ophthalmology A Competency-based Approach - Lee, Andrew G.; Beaver, Hilary A. (Springer New York : Imprint: Springer, 2010)
The elderly patient is not simply an "older adult." Geriatric patients have unique responses to treatment and disease: they often harbor co-morbidities that can impact evaluation, treatment, and prognosis. Often elderly patients may require specialized expertise or experience to deal with specific geriatric syndromes. It is not the goal of Geriatric Ophthalmology to make ophthalmologists into geriatricians. Rather, it is our hope that by applying a competency-based approach, we can improve awareness, increase understanding and encourage expertise about geriatric issues among eye care professionals. Among the topics of special interest to the ophthalmologist treating elderly patients, the editors have included diabetic retinopathy, age-related macular degeneration, cataracts, glaucoma, and low vision. As demographic trends demonstrate, the patient population of will continue to expand into the foreseeable future, making the competent and compassionate care of elderly patients an imperative for clinicians, public health officials, patients and families. Geriatric Ophthalmology: A Competency-Based Approach aims to provide the framework for quality patient care.